Inspiratory muscle strength training for lowering blood pressure and improving endothelial function in postmenopausal women: comparison with “standard of care” aerobic exercise - Craighead, Daniel H.; Freeberg, Kaitlin A.; McCarty, Narissa P.; Rossman, Matthew J.; Moreau, Kerrie L.; You, Zhiying; Chonchol, Michel; Seals, Douglas R. (Frontiers in Physiology, 2022)
Background: High blood pressure (BP), particularly systolic BP (SBP), is the major modifiable risk factor for cardiovascular diseases and related disorders of aging. SBP increases markedly with aging in women such that the prevalence of above-normal SBP (i.e., ≥120 mmHg) in postmenopausal women exceeds rates in age-matched men. This increase in SBP is associated with vascular endothelial dysfunction, mediated by excessive reactive oxygen species-induced oxidative stress and consequent reductions in nitric oxide bioavailability. Moderate-intensity aerobic exercise is a recommended lifestyle strategy for reducing SBP. However, adherence to aerobic exercise guidelines among postmenopausal women is low (<30%) and aerobic exercise does not consistently enhance endothelial function in estrogen-deficient postmenopausal women. High-resistance inspiratory muscle strength training (IMST) is a time-efficient, adherable lifestyle intervention that involves inhaling against resistance through a handheld device (30 breaths/day). Here, we present the protocol for a randomized controlled trial investigating the efficacy of 3 months of high-resistance IMST compared to guideline-based, “standard-of-care” aerobic exercise training for decreasing SBP and improving endothelial function in estrogen-deficient postmenopausal women with above-normal SBP (120-159 mmHg) at baseline (ClinicalTrials.gov Identifier: NCT05000515). Methods: A randomized, single-blind, parallel-group design clinical trial will be conducted in 72 (36/group) estrogen-deficient postmenopausal women with above-normal SBP. Participants will complete baseline testing and then be randomized to either 3 months of high-resistance IMST (30 breaths/day, 6 days/week, 75% maximal inspiratory pressure) or moderate-intensity aerobic exercise training (brisk walking 25 minutes/day, 6 days/week, 40-60% heart rate reserve). Outcome measures will be assessed after 3 months of either intervention. Following end-intervention testing, participants will abstain from their assigned intervention for 6 weeks, after which BP and endothelial function will be assessed to evaluate the potential persistent effects of the intervention of the primary and secondary outcomes. Discussion: This study is designed to compare the effectiveness of time-efficient, high-resistance IMST to guideline-based aerobic exercise training for lowering SBP and improving endothelial function, and interrogating potential mechanisms of action, in estrogen-deficient postmenopausal women.